2022
DOI: 10.36349/easms.2022.v05i10.002
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Lower Gastro-Intestinal Bleeding

Abstract: Background: Rectal bleeding is considered an important sign of colonic disease, particularly colorectal cancer. Rectal bleeding is considered to be an alarm feature in particular for colorectal cancer that, in tum, is the second- leading cause of cancer death globally. Colonoscopy has been reported recently as cost effective method of evaluating asymptomatic rectal bleeding 14, while rectal bleeding as a diagnostic indicator has been questioned in general practice. Objective: The objective of this study is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Numerous studies in the world were conducted regarding bleeding per rectum. Some studies conducted in our country have shown a different etiological pattern from that of Westernized countries (15), where diverticulosis being the commonest cause (6,16,17), followed by ischemic colitis, carcinoma, polyp, and then ulcers. This may be attributed to that the pattern of rectal bleeding causes in the Iraq might be different in their incidences than those in Western countries (15,18).…”
Section: Discussionmentioning
confidence: 70%
“…Numerous studies in the world were conducted regarding bleeding per rectum. Some studies conducted in our country have shown a different etiological pattern from that of Westernized countries (15), where diverticulosis being the commonest cause (6,16,17), followed by ischemic colitis, carcinoma, polyp, and then ulcers. This may be attributed to that the pattern of rectal bleeding causes in the Iraq might be different in their incidences than those in Western countries (15,18).…”
Section: Discussionmentioning
confidence: 70%